Pengaruh Konsentrasi Pupuk Organik Cair (POC) dan Pupuk Hayati Terhadap Pertumbuhan dan Hasil Tanaman Terung Ungu (Solanum melongena L.) - Arief, Arsarizky; Pribadi, Didik Utomo; Hidayat, Ramdan (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: The purple eggplant is a vegetable commodity that highly favored by many people due to it is delicious taste and benefical nutrition content for health. The demand of purple eggplants increased significantly every year, but it is often not matched by an increase in production caused by poor cultivation. The increased production can be achieved through several efforts, one of which is fertilization with organic materials. This research aims to determine the optimal combination and concentration of each treatment for the application of liquid organic fertilizer (LOF) and biological fertilizer which can provides the best influence on plant growth and yield of purple eggplant. Methods: This research used a completely randomized design (CRD) consisting of 2 factors. The first factor was the concentration of liquid organic fertilizer (N) divided into 3 levels, consists of 0 ml/l (N0), 4 ml/l (N1), and 8 ml/l (N2). The second factor was the concentration of bio-fertilizer (P) divided into 4 levels, consists of 0 ml/l (P0), 10 ml/l (P1), 20 ml/l (P2) and 30 ml/l (P3). Results: The result indicated that the concentration of 8 ml/l LOF and 30 ml/l bio-fertilizer was able to increase the number of leaves, total flowers per plant, total fruits per plant, and total fruits fresh weight per plant. Conclusions: This Research can be concluded that the concentration of 8 ml/l LOF and 30 ml/l bio-fertilizer gave the best effect on purple eggplants.